3D Concrete Printing Technology 2019
DOI: 10.1016/b978-0-12-815481-6.00009-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Structures 3D-Printed With Cementitious Powders

Abstract: The three dimensional (3D) printing technology has undergone rapid development in the last few years and it is now possible to print engineering structures. This paper presents a study of the mechanical behavior of 3D printed structures using cementitious powder. Microscopic observation reveals that the 3D printed products have a layered orthotropic microstructure, in which each layer consists of parallel strips. Compression and flexural tests were conducted to determine the mechanical properties and failure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The direction of loading of the printed specimen has influence on the strength properties, as shown in Table II and Figures 13(a) and (b) (Feng et al, 2015). By testing parallel to the layer deposition [see testing direction I in Figure 12(a)], Feng et al (2015) found higher compressive strength than when testing perpendicular to the layer depositions, as shown in Figure 12(a) and Figure 13. This phenomenon is difficult to explain.…”
Section: Compressive and Flexural Strength Of 3d Printing Of Concretementioning
confidence: 99%
See 1 more Smart Citation
“…The direction of loading of the printed specimen has influence on the strength properties, as shown in Table II and Figures 13(a) and (b) (Feng et al, 2015). By testing parallel to the layer deposition [see testing direction I in Figure 12(a)], Feng et al (2015) found higher compressive strength than when testing perpendicular to the layer depositions, as shown in Figure 12(a) and Figure 13. This phenomenon is difficult to explain.…”
Section: Compressive and Flexural Strength Of 3d Printing Of Concretementioning
confidence: 99%
“…This phenomenon is difficult to explain. It is noteworthy that they heat cured their specimens and tested at the young age of 3 h. The failure mechanism of printed cubes under compression test was also investigated by the Feng et al (2015). Specimen loaded in X, Y and Z directions as shown in Figure 13 had almost similar failure patterns.…”
Section: Compressive and Flexural Strength Of 3d Printing Of Concretementioning
confidence: 99%
“…This simplification has brought a brand new way of rapid prototyping for designers. Applications of AM can be found in industries such as automobile (Rahim and Maidin, 2014), aerospace (Straub, 2014), biomedical (Bhuthalingam et al, 2015) and construction (Feng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Singh and Rupinder classified technological development of prototyping into three phases – manual prototyping by a skilled craftsman, soft prototype with the aid of a computer software around mid-1970s and RP applied to casting applications in the early 1980s (Singh, 2009). Usually, as shown in Figure 1, there are two main approaches – AM and SM – for the manufacture of a sand mould (Shan et al , 2007; Feng et al , 2015). The typical rapid sand casting approaches include the following: SL, SLS, FDM, LOM, 3DP and drop-on-drop deposition inkjet printing technology (Singh, 2009; Feng et al , 2015; Chhabra and Singh, 2011; Wong and Hernandez, 2012), as well as patternless casting manufacture technology (PCM) (Yang, 2003; Bassoli et al , 2007; Singh, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…3D sand mould printing fabricates pattern and core boxes without pattern mould, which is different from direct and indirect tooling approach. Existing technologies of 3D sand mould printing mainly are the following three methods: SLS, 3DP and PCM (Singh, 2009; Feng et al , 2015; Chhabra and Singh, 2011), and companies applying these methods include EOSINT-SLS, Soligen-DSPC, Generis (GS), ProMetal rapid casting technology (RCT), ZCast 501 and Fenghua Zhuoli-PCM, etc. (Shan et al , 2007; Chhabra and Singh, 2011).…”
Section: Introductionmentioning
confidence: 99%